2017
DOI: 10.1509/jim.16.0031
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Bilateral Norms on SMEs’ Export Relationships: A Dynamic Perspective

Abstract: Prior research has established the pivotal role of bilateral norms in relationship marketing, identifying them as effective relational governance mechanisms that firms can use to manage their international alliances with overseas intermediaries. Unfortunately, few studies have examined differential effects of specific norms on positive and negative behaviors, let alone norms’ effectiveness in the harsh export context of resource-constrained small and medium-sized enterprises (SMEs). To address these gaps, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 82 publications
(149 reference statements)
0
32
1
Order By: Relevance
“…Relatedly, extending the PLS-SEM algorithm to accommodate binary dependent variables would provide an opportunity to consider endogeneity methods specific to such model settings, such as the control function approach and its extensions (e.g., Garen 1984;Wooldridge 2015). These kinds of advances would be particularly beneficial for international marketing research, which frequently relies on longitudinal and panel data (e.g., Kumar and Pansari 2016), as well as binary outcome variables (e.g., Obadia et al 2017;Westjohn et al 2017). (Gui et al 2017) package supports the Gaussian copula approach The REndo (Gui et al 2017) package supports LIV model with one dependent and one independent variables 48 FIGURES * Consider continuing at Stage 3 and use the Gaussian copula approach to assess to what extent the endogeneity problem has been successfully addressed by the model.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, extending the PLS-SEM algorithm to accommodate binary dependent variables would provide an opportunity to consider endogeneity methods specific to such model settings, such as the control function approach and its extensions (e.g., Garen 1984;Wooldridge 2015). These kinds of advances would be particularly beneficial for international marketing research, which frequently relies on longitudinal and panel data (e.g., Kumar and Pansari 2016), as well as binary outcome variables (e.g., Obadia et al 2017;Westjohn et al 2017). (Gui et al 2017) package supports the Gaussian copula approach The REndo (Gui et al 2017) package supports LIV model with one dependent and one independent variables 48 FIGURES * Consider continuing at Stage 3 and use the Gaussian copula approach to assess to what extent the endogeneity problem has been successfully addressed by the model.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should try to identify actions that firms can take to move between different relationship stages as a result of economic change. Sharing information pertaining to trading partner needs and strategic focus during times of instability will likely result in enhanced partner goodwill along with an effective response to market changes (Obadia, Vida, and Pla-Barber 2017;Sousa and Tan 2015). Specifically, firm subsidiaries are increasingly requesting information to improve the value creation process (Cenamor et al 2017).…”
Section: Implications For Future Exporting Theory From Recent Researchmentioning
confidence: 99%
“…In effect, greater emphasis on this issue is required. Obadia, Vida, and Pla-Barber (2017) found that when small and medium enterprises partner with host market intermediaries they can decrease opportunistic behavior, thus reducing costs and maintaining valued relationships. Relational norms promote information exchange.…”
Section: Implications For Future Exporting Theory From Recent Researchmentioning
confidence: 99%
“…Opportunism finds particularly fertile ground in international buyer–seller relationships, due to the geographic and cultural distance between the interacting parties, which creates information asymmetries and difficulties in exposing and verifying opportunistic acts (Katsikeas, Skarmeas, and Bello 2009; Li and Ng 2002; Luo, 2009). A foreign partner behaving opportunistically can create conflict (Barnes et al 2010), fuel suspicion about trustworthiness (Katsikeas, Skarmeas, and Bello 2009), and decrease overall relationship effectiveness (Obadia, Vida, and Pla-Barber 2017). Although emotionally intelligent exporters are able to regulate emotions to maintain a positive atmosphere in the working relationships with importers, opportunistic behavior is still difficult to detect.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%